Analysis of Teaching Patterns and Language Acquisition Using the Social-Emotional Learning - Fahkrunisa, Lulu; Sulistiawati, Ira; Perwitasari, Tuhu; Rizky, Reffy Ananda (Jurnal Bahasa Inggris, 2024)
This study explores the integration of Social Emotional Learning (SEL) principles into English language teaching and its influence on Second Language Acquisition (SLA). Conducted at MTs Ainal Yaqin in Jambi, Indonesia, the research employed a qualitative multiple case design involving classroom observations and semi structured teacher interviews. Thematic analysis identified key teaching patterns that align with SEL principles including creating a supportive and safe learning environment, building positive teacher–student relationships, providing positive reinforcement, fostering peer collaboration, and integrating SEL based strategies such as storytelling, role play, and project-based learning. Findings reveal that these practices contribute to lowering students’ anxiety, increasing motivation, and improving willingness to communicate which in turn enhance linguistic competence and socio emotional growth. The results align with Krashen’s Affective Filter Hypothesis, sociocultural perspectives, and the CASEL Framework, highlighting that reduced anxiety and emotional security foster more effective language acquisition. Despite challenges such as time constraints and varied emotional regulation abilities among students, the outcomes including greater fluency, improved vocabulary mastery, heightened engagement, and stronger interpersonal skills demonstrate the transformative potential of embedding SEL strategically into English language instruction.